A Preliminary Analysis of the Factors Affecting Satisfaction with the Police Practicum Credit Program in South Korea. Issue 1 (2nd January 2018) - Cho, Joon Tag; Park, Hyeonho
Abstract : Numerous studies have been conducted about criminal justice internship programs in western countries, but few have addressed similar types of programs conducted in Eastern countries. To fill this gap in the literature, this study preliminarily analyzed the factors affecting satisfaction with the police practicum credit program in South Korea using data collected from 208 participating students and police officers. The results showed that participants were generally satisfied with the program but had different perceptions about each program component. Focusing on the crucial elements affecting overall satisfaction with the program, the study examined the following factors: the curriculum; the period and practice time; the proportion of on-site practice; teaching material; credits; and police officers' preparedness, attitudes and information offerings. Our results suggest that the curriculum and preparedness of the officers in charge were significant factors affecting the participants' satisfaction. Based on the findings, implications for policy recommendations are discussed.